The pharmacokinetics of three doses of budesonide/glycopyrronium/formoterol fumarate dihydrate metered dose inhaler compared with active controls: A Phase I randomized, single-dose, crossover study in healthy adults. (June 2018) - Darken, Patrick; DePetrillo, Paolo; Reisner, Colin; St Rose, Earl; Dorinsky, Paul
Abstract: The budesonide/glycopyrronium/formoterol fumarate dihydrate metered dose inhaler (BGF MDI) is an inhaled corticosteroid/long-acting muscarinic antagonist/long-acting β2 -agonist fixed-dose combination formulated with innovative co-suspension delivery technology that is in clinical development for the treatment of chronic obstructive pulmonary disease (COPD). This randomized, Phase I, single-dose, six-treatment, four-period, crossover study (NCT01980615) examined the pharmacokinetic (PK) and safety profile of three doses of BGF MDI (320/14.4/10 μg [equivalent to budesonide/glycopyrrolate/formoterol fumarate 320/18/9.6 μg], 160/14.4/10 μg and 80/14.4/10 μg), two doses of a budesonide/formoterol fumarate dihydrate fixed-dose combination (BUD/FORM MDI 320/9 μg and 160/9 μg; not using co-suspension delivery technology) and a glycopyrronium/formoterol fumarate dihydrate co-suspension delivery technology MDI (GFF MDI 14.4/10 μg) in healthy volunteers (18–45 years of age). PK parameters included area under the plasma concentration–time curve from 0 to 12 h (AUC0–12 ), AUC up to the last measurable concentration (AUC0–t ), maximum plasma concentration (Cmax ) and time to maximum plasma concentration (tmax ). Safety was monitored throughout the study. Of 84 subjects randomized, 76 completed the study. BGF MDI 320/14.4/10 μg was bioequivalent to BUD/FORM MDI 320/9 μg for budesonide for Cmax, AUC0–12 and AUC0–t (primary objective). Dose proportionality was observed for the budesonide component between BGF MDI 80/14.4/10 μg and BGF MDI 160/14.4/10 μg, and between BGF MDI 160/14.4/10 μg and BGF MDI 320/14.4/10 μg. Systemic exposure to glycopyrronium and formoterol after BGF MDI 320/14.4/10 μg treatment was similar to GFF MDI 14.4/10 μg. The rate of adverse events was 3.7–17.9% across treatments without any serious adverse events. In conclusion, BGF MDI 320/14.4/10 μg had a similar budesonide PK profile to BUD/FORM MDI 320/9 μg. No PK drug–drug interactions were observed when budesonide was added to glycopyrronium and formoterol fumarate dihydrate. These data support the use of budesonide 320 μg and 160 μg in future clinical trials of BGF MDI in COPD.